The histone chaperone SPT2 regulates chromatin structure and function in Metazoa - Saredi, Giulia (Nat Struct Mol Biol, 2024)
Histone chaperones control nucleosome density and chromatin structure. In yeast, the H3–H4 chaperone Spt2 controls histone deposition at active genes but its roles in metazoan chromatin structure and organismal physiology are not known. Here we identify the Caenorhabditis elegans ortholog of SPT2 (CeSPT-2) and show that its ability to bind histones H3–H4 is important for germline development and transgenerational epigenetic gene silencing, and that spt-2 null mutants display signatures of a global stress response. Genome-wide profiling showed that CeSPT-2 binds to a range of highly expressed genes, and we find that spt-2 mutants have increased chromatin accessibility at a subset of these loci. We also show that SPT2 influences chromatin structure and controls the levels of soluble and chromatin-bound H3.3 in human cells. Our work reveals roles for SPT2 in controlling chromatin structure and function in Metazoa.